Delayed expulsion of a large fibroid after transcervical radiofrequency ablation: A case report - Elvin Piriyev, MD; Thomas Römer, MD (Radiology Case Reports, 2023)
Fibroids are the most common type of benign uterine tumor, which occur up to 68.6% of women. Hypermenorrhea is the most common symptom with a general prevalence of 40%-54%, followed by dysmenorrhea and low abdominal pain. Transcervical fibroids ablation was developed as a minimally invasive, incisionless treatment of fibroids in a short time. This method is safe and effective with an excellent record of safety. We present the case of a 40-year-old woman, who attended in our fibroid excellence center. She reported severe hypermenorrhea and dysmenorrhea. Family planning was definitely completed. Using vaginal ultrasonography a FIGO 2-5 fibroid of 5 cm in diameter was detected. Different treatment options were discussed: medical treatment, laparoscopic fibroidectomy, hysterectomy, and transcervical radiofrequency ablation with Sonata System. Because of advantages of transcervical radiofrequency ablation (minimal invasive treatment without incision, effectivity of method, short surgical time) the patient decided on this method. Three months later, the patient came to the first follow up. She reported a significant improvement of hypermenorrhea. A vaginal ultrasonography was carried out. The fibroid changed its position from FIGO 2-5 to FIGO 2. The patient was very satisfied with the result. After 2 months, she attended in our department again because of severe clear vaginal discharge. She had no bleeding, no pain as well as no fever. We examined her immediately. A fibroid expulsion was detected. The fibroid was removed vaginally. There was no severe bleeding during the operation and the fibroid could be removed completely. The surgery time was 25 minutes.